TAXONOMIC ANALYSIS OF POPULATIONS OF SABANEJEWIA VLADYKOV, 1929 (TELEOSTEI: COBITIDAE) IN THE ARAL SEA BASIN (Scientific journal of the Fergana State University, 2024)
Sabanejewia aralensis is considered the sole representative of its genus within the Aral Sea basin and is widely distributed in the Amudarya and Syrdarya basins and its various tributaries. Despite its widespread distribution, this species harbors a complex taxonomic history, with conflicting views regarding its precise classification. The results of the preliminary phylogenetic analysis based on the mitochondrial cytb gene suggests a hidden diversity within this species. The data hint at the potential existence of three distinct species currently masquerading under the single name Sabanejewia aralensis.